Analysing sentences an introduction to English syntax - Burton-Roberts, Noel 1948- (Learning about language, 2016)
In this fourth edition, Analysing Sentences has been thoroughly revised and now features a brand new companion website with additional activities and exercises for students and an answer book for the in-text exercises for professors. The extra activities on the website give students practice in identifying syntactic phenomena in running text and will help to deepen understanding of this topic